Response of rice genotypes under different zinc fertilization strategy - Ramani, VP; Kumar, Dileep; Shukla, AK; Patel, RA (ORYZA-An International Journal of Rice, 2019)
Soil zinc (Zn) deficiency limits crop growth and yield besides its low concentration in grain and straw. Growing of Zn efficient cultivars with high crop yield at low Zn supply would represent a sustainable approach to crop production. Therefore, to evaluate Zn efficiency of rice genotypes, twenty eight different rice genotypes were evaluated under various treatments like three levels of Zn viz. low (without Zn), medium (10 kg Zn ha-1 soil) and high (20 kg Zn ha-1 soil + three foliar sprays of 0.5% Zn). Zinc efficiency index of all genotypes ranged from 65.5 to 102.6 % and Zn uptake efficiency ranged from 53.8 to 107 % with a mean value of 87.1 and 76.5 %. Cultivar GR-101 was having the highest Zn efficiency index as well as Zn efficiency compared to other genotype. Based on grain yield and Zn efficiency, the genotypes Ashoka-20, Narmad, GR-12, GR-3, GR-1 and GR-2 were classified as efficient and responsive, genotypes GR- 11, SLR -51214. GAUR-10 and GR-13 as efficient and non responsive, whereas, genotypes GR-101, GR-104, GR-102 and Lalkad as inefficient and responsive. The Gurjari, AAUDR-1, K-Kamod, GR-9, GR-5, P-2003 SK-20 and GR-7 genotype were classified as inefficient and non responsive. The efficient and responsive genotypes are most desirable as they would produce higher yield under low Zn concentration in soil and responded well under external application of Zn sources.